دراسة وبائية لداء الكيسات المائية في الأغنام والماعز والأبقار بمحافظة اللاذقية في سوريا - جبلاوي, رفيق جميل; دريوس, محمد علي (Latakia University Journal -Biological Sciences Series, 2019)
من أجل التقصي عن واقع داء الكيسات المائية في القطر العربي السوري تم فحــص (1515) رأسا" من الأبقار و( 14302) رأسا" من الأغنام و( 1650) رأسا" من الماعز المذبوحة في مسلخ محافظة اللاذقية وقد بينت النتائج أن نسبة الإصابة بالكيسات المائية قد بلغت (4,2 %, 6,9 %, 12,7 %) عند الأبقار والأغنام والماعز على التوالي . تواجدت الإصابة في الكبد أو الرئة أو في العضوين معا". ووجد أن الإصابة في الكبد أكثر مما هي عليه الحال في الرئة عند الأغنام والماعز, وفي كلا العضوين عند الأبقار. وكانت كافة الكيسات المشاهدة (المخصبة والعقيمة والمتجبنة أو المتكلسة) من النوع الوحيد المسكن. وقد بينت الدراسة أن نسبة الإصابة تزداد مع تقدم الحيوان بالعمر. In this study, 1515 slaughtered cattle, 14302 Awassi sheep and 1650 goats have been searched for the presence of Hydatid – cysts. As a result of this investigation, 4.2 % of cattle, 6.9 % of sheep and 12.7 % of goats were found to be infected with Hydatid – Cysts . All Hydatid – Cysts were unicolor ones and they were found either in the Liver or in the Lung and the extensity of infection was more frequent in the Liver than in the Lung in sheep and goats, while it was more frequent in both of the Liver and Lung in cattle . All Kinds of Hydatid – Cysts such as the fertilized, sterilized, classified, or caseinied were found in this investigation. It was also found that the rate of infection was significantly increased with age of animal .